Sperm Cryopreservation Protocols for Neotropical South American Species - Streit, Danilo P.; Rodrigues, Rômulo Batista; Sanches, Eduardo Antônio [UNESP]; Povh, Jayme Aparecido; de Siqueira-Silva, Diógenes Henrique; Vasconcelos, Ana Carina Nogueira; Zhang, Tiantian (Taylor & Francis, 2024)
Since South American Neotropical fish species began to be studied in the early 1980s, nine research groups developed studies involving these species. In total, 137 scientific articles have been published so far with species from six families. The most studied intracellular cryoprotectant for these species was DMSO, followed by methanol and methylglycol, while glucose was the most used extender, followed by Beltsville Thawing Solution (BTS) and egg yolk. The most advanced and extensively tested protocols were observed in the species: Prochilodus lineatus, Rhamdia quelen, and Brycon orbignyanus. On the other hand, Colossoma macropomum, is the second South American species with the largest number of studies developed with seminal cryobiology, although the protocols are not yet considered consolidated.